INJURY AND ILLNESS PATTERNS IN COMPETITIVE SAILORS OF THE INTERNATIONAL SAILING FEDERATION SAILING WORLD CHAMPIONSHIPS 2014 – A 12-MONTH RETROSPECTIVE STUDY. Issue 4 (1st February 2017) - Leong, Darren; Tan, Ben; Pardal, Carmen Vaz; Lin, Cindy; Kam, Jia Wen
Abstract : Background: Olympic Sailing events have evolved to include quicker and more physically demanding boats, stirring interest in the injury patterns and associations amongst sailors of these boats. Objective: To characterise sailing-related injuries and illnesses among sailors participating in the ISAF 2014 World Championships. Design: Retrospective descriptive study. Setting: The International Sailing Federation (ISAF) World Championships is a top tier competition bringing together 1167 sailors in all 10 Olympic classes. The Sailing World Championships 2014 were held in Santander, Spain. Patients (or Participants): Sailors registered for the 2014 ISAF World Championships were surveyed via an interviewer-administered questionnaire from June to September 2014 (off-site prior to competition; and on-site during competition). This was a 12-month recall questionnaire on sailing-related injuries and illnesses. Interventions (or Assessment of Risk Factors): Gender, position (helm, crew), sailing class, training volume, part of boat contributing to injury, and actions performed during sailing. Main Outcome Measurements: The occurrence or non-occurrence of sailing-related injuries and illnesses; the number of injuries; injury site, type, cause/mechanism; injury prevalence and severity; and contributing factors to injury. Results: There were 760 respondents (65% of all participants) for the 12-month recall questionnaire (58% male, 42% female), of whom 244 participants reported 299 injuries (0.59 injuries per 1000 h of sailing). Injuries were most prevalent in the 49erFX (64%), RS:X Women (39%), 49er (37%) and Nacra 17 (36%). Lower back (29% of sailors), knee (13%), shoulder (12%) and ankle (10%) injuries were most prevalent; most (58% of all injuries) were overuse injuries; and 56% of sailors lost sailing time. Most illnesses (40%) were infections, primarily of the respiratory system (43%). Conclusions: The Olympic classes introduced since 2000 (49erFX, 49er, Nacra 17) report more injuries. These injuries were mainly traumatic events, compared with overuse injuries in the other classes.